Laparoscopic Sleeve Gastrectomy in Situs Inversus Totalis: a Case Report - Yazar, FM; Emre, A; Akbulut, S; Urfalioglu, A; Cengiz, E; Sertkaya, M; Yildiz, H; Bulbuloglu, E (2016)
The aim of this study is to review the reliability of laparoscopic obesity operations in patients with situs inversus totalis(SIT). A new case of SIT was presented together with a literature review of published English language studies on laparoscopic gastric banding (LAGB), laparoscopic gastric bypass (LRYGB), laparoscopic sleeve gastrectomy (LSG), laparoscopic obesity surgery (LOS), and SIT, accessed via PubMed and Google Scholar databases. The case is presented of a 21-year-old female patient who underwent LSG due to SIT. A total of 12 publications in literature matched the search criteria for LAGB, LRYGB, LSG, LOS, and SIT, which reported LAGB in five cases, LRYGB in four cases, and LSG in four cases. In the rare event of SIT, LOS can be safely used following good evaluation. C1 [Yazar, Fatih Mehmet; Emre, Arif; Cengiz, Emrah; Sertkaya, Mehmet; Bulbuloglu, Ertan] Kahramanmaras Sutcu Imam Univ, Dept Gen Surg, TR-46050 Kahramanmaras, Turkey. [Akbulut, Sami] Inonu Univ, Dept Gen Surg, Fac Med, Malatya, Turkey. [Urfalioglu, Aykut; Yildiz, Huseyin] Kahramanmaras Sutcu Imam Univ, Dept Anestesiol, TR-46050 Kahramanmaras, Turkey.